Scurvy in an 11-year-old boy. Case report. - Montero, D.; Lamberti , M.; Irurzun, I.; Massimo, J.A. (European Journal of Pediatric Dermatology, 2022)
Scurvy is a rare disease in the pediatric population and occurs as a result of vitamin C deficiency, mainly in children with restrictive diets. A case of scurvy was reported in an 11-year-old boy with feeding problems who presented general symptoms and mucocutaneous, musculoskeletal and hematological manifestations.